2015
DOI: 10.3389/fmars.2015.00056
|View full text |Cite
|
Sign up to set email alerts
|

Footprints of climate change on Mediterranean Sea biota

Abstract: The Mediterranean Sea ranks among the ocean regions warming fastest. There is evidence for impacts of climate change on marine Mediterranean organisms but a quantitative assessment is lacking. We compiled the impacts of warming reported in the literature to provide a quantitative assessment for the Mediterranean Sea. During the last three decades the summer surface temperature has increased 1.15 • C. Strong heat wave events have occurred in years 1994, 2003, and 2009. Impacts of warming are evident on growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(160 citation statements)
references
References 37 publications
5
151
1
3
Order By: Relevance
“…In addition, they are, like in the present case, often characterized by distinctive ecological characteristics that need to be preserved against the negative impact of environmental modifications, such as those observed and predicted as a consequence of climate change, especially in the Mediterranean Sea (e.g. Marb a et al, 2015). Finally, sabellariid reefs are the focus of recent attempts to restore their habitats where degraded (e.g.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, they are, like in the present case, often characterized by distinctive ecological characteristics that need to be preserved against the negative impact of environmental modifications, such as those observed and predicted as a consequence of climate change, especially in the Mediterranean Sea (e.g. Marb a et al, 2015). Finally, sabellariid reefs are the focus of recent attempts to restore their habitats where degraded (e.g.…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, water flow is the lowest range on river JJA season, this could not significantly impact SST variability western parts of at bay. Marbà et al (2015) investigated SST change and their impacts on marine ecosystem period of . They also reported summer season average SST increased 1.15 °C for the period.…”
Section: Discussionmentioning
confidence: 99%
“…A change in SST affects several biophysical, biochemical processes in the marine ecosystems and also between the atmosphere and marine ecosystems (Guldberg & Bruno, 2010;Halpern et al, 2015). Marbà et al (2015) investigated impacts of SST changes on marine biota in Mediterranean Sea by using AVHRR Pathfinder version 5.2 remote sensed SST data, which have 10x10 km high spatial and daily temporal resolution during the period 1980-2011. In this study, it was reported that the SST has been raised 0.25°C per decade and 0.65 ºC from eastern to western in the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of climate change is likely increasing (e.g., Marbà et al 2015) and may change the way human activities impact marine ecosystems, compounding the understanding of how marine ecosystems will evolve and respond to human pressures in the near future. Processes and events that occur over long timescales, and are not easily identifiable, may significantly constrain management of marine ecosystems.…”
Section: Scientific Research Needs To Address Challenges To Biodiversitymentioning
confidence: 99%
“…Traditional conservation planning has traditionally overlooked or indirectly considered the strong connections between different environments (Álvarez-Romero et al 2011, Mateos-Molina et al 2015). Yet, transitional and freshwater ecosystems are also an integral part of the land-sea connection.…”
Section: Scientific Research Needs To Address Challenges To Biodiversitymentioning
confidence: 99%